Calculation Method of Overburden Damage Height Based on Fracture Mechanics Analysis of Soft and Hard Rock Layers. (27th February 2019) - Chen, Liang; Fan, Shaowu; Zhao, Can; Zhang, Lang; Cheng, Zhiheng
Abstract : Under the geological condition of soft and hard rock interaction stratum, the overburden damage height can provide a quantitative support for the design of the locations of gas drainage boreholes in the roof mining fracture zone and the determination of the hydraulic fracture zone in coal seam mining. The interbedded structure of overlying mud rock and sandstone in the Lu'an mining area in Shanxi is a typical soft and hard rock interaction stratum. In view of the lack of soft rock fracture mechanics analysis and the improper calculation of the damage height of overburden rock caused by constant rock residual bulking coefficient to be used regularly in the analysis, in this paper, we constructed a fracture model of soft and hard strata by giving a quantitative classification criterion of soft and hard rocks and introducing a fracture failure criterion of soft rock strata and the space constraint condition of broken-expansion rock formation. Aiming at improving the calculation precision of overburden damage height, we presented a calculation method based on fracture mechanics analysis of soft and hard strata, which could delineate the extent of intact rock in overlying strata from bottom to top to determine the damage height of overburden rock. This research took Yuwu coal mine in Lu'an mining area as an example. Results showed that (1) by the calculation method, the overburden damage height of the N1102 fully mechanized caving face in Yuwu coal mine was 51.44 m, which was less than the value obtained by an actual borehole TV method as well as the numerical simulation result of 53.46 m, with a calculation accuracy about 96.22%, which is quite high for both. The calculation accuracy of the proposed method was higher than that of the three conventional theoretical methods, and it effectively solved the limitation of the fracture analysis method without the inclusion of the soft rock layer in design and the distortion problem due to the residual bulking coefficient to be improperly used in simulation. (2) There was no noticeable fractures in the broken soft rock zone, and the whole fractures were mainly low-angle rupture; the fractures in hard rock layer had obvious ruptures and multiangle cracks, and the average fracture width of soft rock was 2.8 mm smaller than that of hard rock. The fracture modes of soft rock and hard rock were mainly tensile failure and tensile shear failure, which verified the correctness of the fracture mechanics model of soft and hard rock layers constructed in this paper. (3) It is noticed that the tensile strength of rock in this method needs to be obtained through rock mechanics experiment on overlying strata in the study area, and our proposed method was applicable to the mining conditions of near horizontal coal seam. The calculation accuracy of this method meets the engineering error requirements and can be applied to the prediction of overburden damage height in near horizontal coal seam mining.